Ninety Years of the Journal – Part 2 - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2025)
The Journal revisits an historic paper from 1974 that reflects on the centenary of the formation of the Society and its associated Journal. Five historic technical papers from the 19th century, reproduced in 1974, have also been extracted.